Intraspecific Competition, Habitat Quality, Niche Partitioning, and Causes of Intrasexual Territoriality for a Reintroduced Carnivoran - Facka, Aaron N.; Powell, Roger A. (Frontiers in Ecology and Evolution, 2021)
Experience and information about resources should be advantageous to the resident of a home range while lack of such information should put invaders into the home range at a disadvantage. Conspecifics, especially, should avoid the home ranges of one another to ensure that they do not experience reduced resource availability caused by resource depression or depletion. Yet, encountering conspecific competitors of different sexes may elicit responses that can lead to spacing on a landscape that has different costs and benefits on males and females. We tested the hypothesis that female fishers (Pekania pennanti) avoid competition from both males and female conspecifics whereas male fishers avoid competition only from other males. We intentionally reintroduced fishers onto our study site in the presence or absence of competitors’ home ranges during late 2009 through 2011. Using satellite transmitters (Argos) and land-based (VHF) telemetry, we monitored fishers and estimated their locations, movements and use of the surrounding landscape during their first 500 days after release. All fishers settled in high quality habitat but females that encountered the home ranges of conspecifics moved farther, explored larger areas, and settled farther from their release locations than did females that did not encounter a conspecific’s home range. Male fishers exhibited diverse responses upon encountering the home ranges of conspecifics. Thus, female fishers avoid conspecific competition from all fishers but males tolerate, or impose, competition with females, apparently to increase mating opportunities. These observations are consistent with the movements and strategies of other solitary carnivores.